2015
DOI: 10.1111/iej.12492
|View full text |Cite
|
Sign up to set email alerts
|

EDTA conditioning of dentine promotes adhesion, migration and differentiation of dental pulp stem cells

Abstract: EDTA conditioning of dentine promoted the adhesion, migration and differentiation of dental pulp stem cells towards or onto dentine. A pre-treatment with EDTA as the final step of an irrigation protocol for regenerative endodontic procedures has the potential to act favourably on new tissue formation within the root canal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
158
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(171 citation statements)
references
References 35 publications
(33 reference statements)
6
158
0
7
Order By: Relevance
“…2 In contrast, a smaller amount of TGF-b1 was found in the NaOCl treatment samples. Although our data broadly corroborate those of other studies showing that EDTA conditioning of dentine promotes migration of dental pulp stem cells, 3 we noticed differences in relation to published data regarding cell migration toward alpha-MEM supplemented with 20% FBS (Control 1). Whereas our study found that the rates of migration toward the media conditioned by tooth slices containing predentin layer and treated with 10% EDTA were similar to those of Control 1, 3 Galler et al (2016) found that cell migration toward the pretreated dentine surface amounted to 70% of the positive migration control (alpha-MEM with 20% FBS).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…2 In contrast, a smaller amount of TGF-b1 was found in the NaOCl treatment samples. Although our data broadly corroborate those of other studies showing that EDTA conditioning of dentine promotes migration of dental pulp stem cells, 3 we noticed differences in relation to published data regarding cell migration toward alpha-MEM supplemented with 20% FBS (Control 1). Whereas our study found that the rates of migration toward the media conditioned by tooth slices containing predentin layer and treated with 10% EDTA were similar to those of Control 1, 3 Galler et al (2016) found that cell migration toward the pretreated dentine surface amounted to 70% of the positive migration control (alpha-MEM with 20% FBS).…”
Section: Discussionsupporting
confidence: 83%
“…Several studies have focused on the regenerative potential of different cytokines and growth factors designed to improve cellular chemotaxis and cell homing into the emptied dental pulp space in vivo. 1,2,3,4,5,6 The dentin matrix is a reservoir of soluble cytokines and growth factors secreted by odontoblasts and pulp fibroblasts, which could be released during tissue demineralization. 1,2,3,4 The dissolution of these cytokines and growth factors can occur pathologically during dental caries and following restorative procedures.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…8,12 Without these growth factors, the intrinsic signals embedded in dentin and liberated by root canal irrigants such as ethylenediaminetetraacetic acid (EDTA) can also produce an apparently functional pulp. 10,13 As a result, the application of the cell homing concept appears efficient to induce repair/ regenerative processes within the pulp space and can therefore circumvent some disadvantages of a natural blood clot.…”
Section: Introductionmentioning
confidence: 99%